Human microbiome and microbiota identification for preventing and controlling healthcare-associated infections: A systematic review - Tozzo, Pamela; Delicati, Arianna; Caenazzo, Luciana (Frontiers in Public Health, 2022)
Objective: This systematic review describes the role of the human microbiome and microbiota in healthcare-associated infections (HAIs). Studies on the microbiota of patients, healthcare environment (HE), medical equipment or healthcare workers (HCW) and how it could be transmitted among the different subjects will be described in order to define alarming risk factors for HAIs spreading and to identify strategies for HAIs control or prevention. Methods: This review was performed in adherence to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. After retrieval in databases, identification and screening of available records, 36 published studies were considered eligible and included in the review. Results: a multifaceted approach is required and the analyses of the many factors related to human microbiota, which can influence HAIs onset, could be of paramount importance in their prevention and control. In this review we will focus mainly on the localization, transmission, and prevention of ESKAPE (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) bacteria and Clostridium difficile which are the most common pathogens causing HAIs. Conclusions: Healthcare workers’ microbiota, patient’s microbiota, environmental and medical equipment microbiota, ecosystem characteristics, ways of transmission, cleaning strategies and the microbial resistome should be taken into account for future studies on more effective preventive and therapeutic strategies against HAIs.